2021
DOI: 10.3390/life11020110
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding: Biological and Social Variables in Different Modes of Conception

Abstract: Background: Breastfeeding has effects on health throughout the lives of mothers and babies. In 2014 in Italy, 10,976 babies were born through ART (assisted reproductive technology), accounting for 2.2% of annual births. The study aims to assess how both social and biological variables and the mode of conception influence breastfeeding. Methods: This observational study involves 161 pregnancies from three different modes of conception: homologous in vitro fertilization, ovum donation, and spontaneous pregnancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The effort we made to have comparable groups with homogeneous clinical characteristics (mothers sharing the double-occupancy room simultaneously, who gave birth to healthy, full-term, singleton infant) and the pragmatic enrollment, coupled with the support given by the same formed team, makes the obtained results reliable. Moreover, these outcomes comply with the previous cited Italian studies 10,16 . Nevertheless, we believe that our study can be further confirmed in a larger investigation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The effort we made to have comparable groups with homogeneous clinical characteristics (mothers sharing the double-occupancy room simultaneously, who gave birth to healthy, full-term, singleton infant) and the pragmatic enrollment, coupled with the support given by the same formed team, makes the obtained results reliable. Moreover, these outcomes comply with the previous cited Italian studies 10,16 . Nevertheless, we believe that our study can be further confirmed in a larger investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Two previous Italian case-control studies 10,16 that examined the association between the mode of conception and breastfeeding outcomes obtained similar results. Cromi et al 16 investigated the initiation, duration and exclusivity of breastfeeding among women who had conceived with the help of ART, compared with a matched control group who conceived spontaneously.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In comparison, on average, respondents who became the control group (not accompanied) managed to do EBI in the third 30 minutes. Information from Table 3 explains that the process of mentoring from the closest person to maternity mothers is strong support psychologically that can mentally awaken pregnant women to face anxiety and realize the importance of love to the baby who will be born in the form of awareness of carrying out EBI [28]- [30].…”
Section: Influence Of Mentoringmentioning
confidence: 99%